Review on role of nrf2 pathway activation in neurological disorder - K, Manisha; K, Loganadhan; M, Aswini; M, Rajesh Kumar; R, Gautham Chakra; K, Swathi Krishna (International Journal of Health Care and Biological Sciences, 2022)
With protein build-up and mitochondrial damage leading to brain problems, oxidative stress is a key factor in the onset of many neurodegenerative illnesses. Several defence systems, including nuclear erythroid factor2 (Nrf2)-Kelch-like ECH-associated protein1, protect nerve cells by producing antioxidants to reduce oxidative stress (Keap1) In a number of neurological illnesses, signalling pathway activation has been shown to be a promising therapeutic for reducing oxidative stress and neuroinflammation and protecting neurons. In this review, we specifically highlight Nrf2’s beneficial effects on Alzheimer’s and Parkinson’s disorders. By releasing over 250 cytoprotective genes intended to combat oxidative stress and neuroinflammation, Nrf2 has demonstrated that it is a master regulator of antioxidants. It has been demonstrated in animal experiments that Nrf2 activation enhances autophagy, mitochondrial biogenesis, and the suppression of inflammatory cytokinin which protects neuronal cells and inhibit progressive neurodegeneration.